A dual-action humanized DKK-1 antibody that activates the Wnt/β-catenin signaling pathway and inhibits the RANKL signaling pathway for osteoporosis therapy - Sheng Hou; Tianyu Gao; Yimei Wu; Hao Wang; Dapeng Zhang; Qingcheng Guo; Jin Xu; Huaizu Guo; Weizhu Qian (Frontiers in Immunology, 2026)
Introduction Osteoporosis remains a major global health challenge, and current single-pathway therapies often fail to achieve coordinated bone remodeling. Dickkopf-1 (DKK-1) is a potent inhibitor of the Wnt/β-catenin signaling pathway and plays a critical role in osteoporotic bone loss. Neutralization of DKK-1 represents a promising therapeutic strategy to promote bone formation while simultaneously inhibiting bone resorption. Methods A humanized anti-DKK-1 monoclonal antibody (IgG4) was generated via CDR grafting combined with structure-guided back-mutations. Its binding affinity and specificity were assessed by ELISA and surface plasmon resonance. The antibody's ability to restore Wnt/β-catenin signaling was evaluated in human bone marrow mesenchymal stem cells (hMSCs) by Western blotting. Osteogenic differentiation and mineralization were assessed by ALP activity assay and Alizarin Red S staining, respectively. An osteoblast-osteoclast Transwell co-culture model was established to evaluate the antibody's effects on osteoclastogenesis via the OPG/RANKL axis, with osteoclast differentiation assessed by TRAP staining and qPCR. Developability properties, including stability and immunogenicity, were also characterized. Results The humanized antibody bound to DKK-1 with high affinity (EC ₅₀ = 32.8 ng/mL, KD = 2.760 × 10 ⁻¹⁰ mol/L) and showed no cross-reactivity to DKK-2, DKK-3, or DKK-4. In hMSCs, the antibody restored Wnt/β-catenin signaling, as evidenced by nuclear β-catenin accumulation, GSK-3β phosphorylation, and c-Myc upregulation, leading to increased ALP activity, OPG secretion, and mineralization. In the Transwell co-culture model, the antibody restored the OPG/sRANKL molar ratio and significantly suppressed osteoclast marker gene expression (ACP5, CALCR, CTSK, ITGB3, MMP9, and NFATC1) as well as TRAP-positive multinucleated cell formation (from 29 ± 5 per field in the undifferentiated control to 2 ± 1 per field in the antibody-treated group). The antibody also exhibited favorable developability properties, including long-term stability at 2 -8°C for over two years and low cellular immunogenicity. Discussion These findings demonstrate that the humanized anti-DKK-1 antibody exerts dual anabolic and anti-resorptive effects through the Wnt/β-catenin/OPG/RANKL axis. This dual mechanism of action positions the antibody as a promising therapeutic candidate for osteoporosis, warranting further preclinical and clinical evaluation.